From the Bottom Up – Flexible Solid State Electrochromic Devices. (5th September 2014) - Jensen, Jacob; Krebs, Frederik C.
<x xml:space="preserve">Abstract</x> Solid‐state flexible polymer‐based electrochromic devices are fabricated continuously by stacking layers in one direction. This novel bottom‐up approach with no need for a lamination step is realized through in situ photo‐crosslinking of the electrolyte using a "curing‐chamber" fitted to a roll‐coater, which lowers the oxygen concentration at the electrolyte surface. This enables fully printed and 2D patterned organic electrochromics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>